Internalisation of Tolerance Values Learners in Indonesia Merdeka Curriculum - Sutarti, Titin; Asrowi, Asrowi; Triyanto, Triyanto; Ramli, Murni (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This research aims to explore the process of internalising the value of tolerance in students in the context of the Merdeka Curriculum in Indonesia. The research method used is a qualitative study with a literature review approach. The results showed that the Merdeka Curriculum pays significant attention to the development of tolerance attitudes in education. The process of internalising the value of tolerance is carried out through an inclusive, dialogical, and experience-based learning approach. In addition, schools through the central role of teachers play an important role in strengthening tolerance values among students. The findings of this study provide a deeper understanding of the educational practices that support the internalisation of tolerance values in the Merdeka Curriculum and contribute to the development of a more inclusive and human values-oriented curriculum in Indonesia.